Synthesis and Photophysical and Electrochemical Properties of Functionalized Mono-, Bis-, and Trisanthracenyl Bridged Ru(II) Bis(2,2′:6′,2″-terpyridine) Charge Transfer Complexes - Adeloye, Adewale O. (Hindawi Publishing Corporation, 2014)
With the aim of developing new molecular devices having long-range electron transfer in artificial systems and as photosensitizers, a series of homoleptic ruthenium(II) bisterpyridine complexes bearing one to three anthracenyl units sandwiched between terpyridine and 2-methyl-2-butenoic acid group are synthesized and characterized. The complexes formulated as bis-4′-(9-monoanthracenyl-10-(2-methyl-2-butenoic acid) terpyridyl) ruthenium(II) bis(hexafluorophosphate) (RBT1), bis-4′-(9-dianthracenyl-10-(2-methyl-2-butenoic acid) terpyridyl) ruthenium(II) bis(hexafluorophosphate) (RBT2), and bis-4′-(9-trianthracenyl-10-(2-methyl-2-butenoic acid) terpyridyl) ruthenium(II) bis(hexafluorophosphate) (RBT3) were characterized by elemental analysis, FT-IR, UV-Vis, photoluminescence, (1)H and (13)C NMR spectroscopy, and electrochemical techniques by elemental analysis, FT-IR, UV-Vis, photoluminescence, (1)H and (13)C NMR spectroscopy, and electrochemical techniques. The cyclic voltammograms (CVs) of (RBT1), (RBT2), and (RBT3) display reversible one-electron oxidation processes at E (1/2) = 1.13 V, 0.71 V, and 0.99 V, respectively (versus Ag/AgCl). Based on a general linear correlation between increase in the length of π-conjugation bond and the molar extinction coefficients, the Ru(II) bisterpyridyl complexes show characteristic broad and intense metal-to-ligand charge transfer (MLCT) band absorption transitions between 480–600 nm, ε = 9.45 × 10(3) M(−1) cm(−1), and appreciable photoluminescence spanning the visible region.